The Influence of Tourist Experience on Local Product Purchase Behavior - NGUYEN, Dac Hung; KHAI, Hoang Nguyen; NGO, Quang Van (Journal of Environmental Management and Tourism; Vol 13 No 6 (2022): JEMT, Volume XIII, Issue 6(62), Fall 2022, 2022)
This study aims to propose and test a conceptual model to clarify the relationship between tourist experience and local product purchase behavior. It also clarifies the moderating relationship of the commemorative factor in the relationship between experience and local product purchase behavior. From there, there are manycontributions in both theoretical and practical aspects. In detail, the tourist experience has 6 components, namely, escape, staff, peace of mind, uniqueness, learning and entertainment. To test the proposed hypothesis, this research applied quantitative method with the data colected from tourists in a mountainous region in Vietnam via questionnaire survey. Finally, 218 valid questionnaires were collected and tested by SPSS sofware and Amos. The results showed that all components of tourist experience have influence on local product purchase, in which the role of staff is the most importance. Moreover, tourist memory contributes as the moderating variable in the relationship between tourist experience and local product purchase.